A Literature Review of Loss and Grief Among Prisoners - Nur Oktavia Hidayati; Syafira Dewi; Vanessa Zian Mentari; Efri Widianti (Jurnal Keperawatan, 2023)
Loss is a state of an individual experiencing the loss of something that previously existed and belonged. Grieving is a subjective condition that follows loss. Among inmates of all ages and genders, inmates' responses and cops to loss and grieving vary. The purpose of this literature review is to find out how the experience and response of loss and grieving inmates. Article searches are conducted using PubMed databases, Sage Journal and Google Scholar. The criteria for inclusion of articles used are full-text articles in English, types of qualitative and quantitative research, articles with a maximum of publication of the last 12 years (2010-2022) and articles focusing on the loss and grieving of prisoners. The search results obtained five articles that meet the inclusion criteria. The results obtained are differences in experience and response to loss and grieving in women, men, and the elderly. Women prisoners experience unresolved grief and a lack of integration and resolution, male inmates struggle to cognitively accept the reality of obituaries and tend to use maladaptive coping strategies in coping with grief within prisons, while elderly inmates persist by utilizing internal and external resources to help them to cope with loss.